The Contribution of Bilingualism to the Enhancement of Arabic Listening and Speaking Skills in Language Instruction - Zikrillah; Erlina, Erlina; Rafli, Zainal; Amrulloh, Muhammad Afif (Jurnal Pendidikan Bahasa, 2025)
Listening (Istima') and speaking (Kalam) skills are essential components of Arabic language instruction in the 21st century. In the Indonesian context, where Arabic is not a native language, bilingualism presents a promising pedagogical strategy to bridge students’ linguistic comprehension gaps. This study aims to examine the contribution of bilingualism—particularly the selective use of Indonesian—in enhancing learners’ istima’ and kalam proficiency. Employing a systematic literature review method, this research analyzed 20 scholarly articles published over the past five years, focusing on the intersection of bilingualism and Arabic language education. The findings indicate that a bilingual approach not only enriches students’ vocabulary and sentence structure but also fosters communicative confidence through conversation practice, debates, and the use of bilingual audio media. Strategies such as the Bilingual Class System, audiolingual methods, and translanguaging were found to enhance student engagement, reinforce linguistic memory, and build self-confidence in using Arabic. This study underscores the importance of curriculum development, bilingual teacher training, and the provision of interactive bilingual learning materials. The main contribution of this article lies in proposing a contextualized, adaptive, and sustainable bilingual-based pedagogical approach for Arabic language learning. Thus, this research not only contributes to the theoretical advancement of bilingualism but also offers practical guidance for improving the quality of Arabic language instruction in Indonesia.